Delivering Better Health Services to Pakistan's Poor - World Bank (Washington, DC, 2013)
Pakistan is not on track to achieve most Millennium Development Goals (MDGs) related to health, nutrition and population. Given its current rate of progress, in 2015 Pakistan's infant mortality rate (IMR) will be 65 deaths per 1,000 live births and the under-five mortality rate (U5MR) will be 78, considerably above the MDG4 targets of 33 and 43 deaths per 1000 births respectively. Pakistan will not achieve the MDG related to nutrition. The review aims to develop a limited set of practical options that will allow the government and other stakeholders to improve the availability and use of health services, especially for the poor. The report mainly focuses on synthesizing the available body of knowledge through review of existing studies, reports and research. The report starts with a description of the health and nutrition status of the population, Pakistan's fertility and growth rates and potential to benefit from a demographic dividend, the burden of diseases and trends in the past few years. The second and third chapters describe the performance of the public health care system over time, including coverage and utilization, quality of care, equity, and patient satisfaction and the impact of national programs. Chapter four discusses the financing of the sector, including overall trends, and the composition of public and private expenditures. Chapter five describes the organization and management of the sector and examines the role of government. Chapter six concludes by summarizing the key challenges facing the sector and suggesting a way forward.